Determination of the the H3 factor in hydrogen isotope ratio monitoring mass spectrometry - Sessions, A. L.; Burgoyne, T. W.; Hayes, J. M. (Anal Chem, 2001)
The H3 factor, K, is a parameter required in high-precision, mass spectrometric analyses of hydrogen isotopic abundances. When H2 is used as the sample gas, R* = R - Ki2, where R* is the true HD/H2 ratio, R is the observed (mass 3)/(mass 2) ion-current ratio, and i2 is the ion current at mass 2. Four different methods for the determination of K were defined and tested under conditions characteristic of isotope ratio monitoring systems. Three of these were peak-based. The fourth employed steady flows of H2 from a conventional inlet system. Results obtained using the latter method were more precise (standard deviation of K = 0.1 versus approximately 0.6 ppm mV(-1) for the peak-based methods). However, use of the resulting values of K for correction of isotope ratio monitoring GC/MS results led to systematic errors as large as 9 per thousand, whereas use of the peak-based values led to no systematic errors. Values of K were only weakly dependent on the pressure of He, declining approximately 5% for each 10-fold increase in P(He). Small variations in partial pressures of H2O and CH4, potential contaminants under isotope ratio monitoring conditions, had no significant effect on values of K.
Sessions, A LBurgoyne, T W Hayes, J M eng 2001/02/24 12:00 Anal Chem. 2001 Jan 15;73(2):200-7.